"Show me the money plan!" - Chard, Chris (SAGE Knowledge. Cases., 2014)
Rich Smith has just signed his last professional contract in the National Hockey League (NHL). He and his wife, Sarah, however have never operated within a budget or devised a plan to ensure their lifestyle will not suffer after Rich retires. To assist them in achieving their goals (no debt and $8 million in investment assets), Rich hires Clarke Redmond of Redtail Sports Management (RSM). This case analyses the actions taken thereafter.